Keistimewaan Taranum Sheikh Muṣṭafā Ismāʻīl: Analisis Kaedah Lagu dan Teknik Suara: The Privilege of Taranum Sheikh Muṣṭafā Ismāʻīl: An Analysis of the Rules of Song and Sound Techniques - Daud, Mahyudin; Wan Abdullah, Wan Hilmi (Jurnal Usuluddin, 2022)
This article explains the method of taranum Sheikh Mustafa Ismail as a result of a comprehensive study of his reading recordings recorded by various parties obtained by researchers. According to sources, the total number of his recordings in the form of taranum and murattal readings is 52,624 hours but what is available today is only 300 hours while the rest was found to have been lost. This abandoned turath treasure has a huge impact on Taranum knowledge where lovers of knowledge make it a reference and guide especially in the rules of song and sound techniques. This study is a library study where data from primary and secondary sources were collected for analysis. The results of the study found that Sheikh Mustafa Ismail has made a great contribution in the knowledge, especially in the rules of song and sound techniques. His melodious melodies and compositions succeeded in conveying the voice of the Qur’an to all corners of the world and bringing people closer to the Qur’an. His method of recitation is also widely followed by most Quranic qaris around the world.